2021
DOI: 10.1002/mnfr.202100007
|View full text |Cite
|
Sign up to set email alerts
|

Chickpea Extract Ameliorates Metabolic Syndrome Symptoms via Restoring Intestinal Ecology and Metabolic Profile in Type 2 Diabetic Rats

Abstract: Scope: Chickpeas have been recognized as a natural Uyghur medicine in Xinjiang (China) for 2500 years. Although the phenotypic effect on obesity or diabetes was authenticated, the mechanism was unclear. This work aims to study the effect of chickpea extract (CE) on metabolic syndrome induced by type 2 diabetes and to reveal its related mechanisms, focusing on intestinal flora and metabolomics. Methods and results: Diabetic rats are induced by a high-fat diet and intraperitoneal injection of streptozotocin. CE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…BCAAs act in the brain as signals of dietary protein intake. L-Leu suppresses food intake and influences signaling systems associated with feeding behavior [ 13 ] and regulation of glucose metabolism [ 8 ]. Additionally, BCAAs and especially L-ile upregulate intestinal and muscular glucose transporters, enhancing glucose consumption and utilization [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCAAs act in the brain as signals of dietary protein intake. L-Leu suppresses food intake and influences signaling systems associated with feeding behavior [ 13 ] and regulation of glucose metabolism [ 8 ]. Additionally, BCAAs and especially L-ile upregulate intestinal and muscular glucose transporters, enhancing glucose consumption and utilization [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strategies for combining plant proteins in order to meet indispensable amino acid requirements while also taking into consideration the critical roles of dispensable/conditionally indispensable amino acids can help to supply adequate high-quality protein, providing health benefits associated with increased intake of plant-based diets and reducing adverse environmental consequences. Legumes are a rich source of plant proteins and are suggested to moderate postprandial glucose levels [ 8 , 9 ]. Combining legumes, seeds and cereals can counter amino acid imbalance and enhance the presence of specific amino acids leading to the production of foods with functional properties which could positively affect postprandial glucose and appetite responses.…”
Section: Introductionmentioning
confidence: 99%
“…Beta diversity instead of alpha diversity could be seen with significant differences and with an operational taxonomic unit (OTUs), an idea with probiotics would confer diabetes prevention and improvement (Umirah et al 2021 ). Lactobacillus plantarum -pMG36e-GLP-1, an engineered strain is a promising diabetes treatment with its positive effects on faecal metabolomic profile and gut microbial composition (Luo et al 2021 ).Chickpea extract as a natural Uyghur medicine in China has prebiotic effects as to the microbiota and metabolomics output and could be used in preventing diabetes (Li et al 2021 ). Cholecystectomy, a surgical removal of the gallbladder intervention was found to alleviate long-term diabetes induced dysbiosis (Wei et al 2021 ).…”
Section: Prospective Study Designsmentioning
confidence: 99%
“…Studies have indicated that HFD-fed mice produce higher levels of pro-inflammatory cytokines in liver and adipose tissue, including TNF-α, IL-1β, and plasminogen activator inhibitor-1 (PAI-1), 4,26 while the production of antiinflammatory cytokines such as IL-10 is reduced in fat mice. 27 Furthermore, mRNA expression of these cytokines was measured after 16 weeks of HFD feeding with or without CPO supplementation. The results showed that the mRNA expressions of TNF-α, IL-1β, IFN-γ and PAI-1 were higher in the liver and adipose tissue of HFD-fed mice compared with chowfed mice, whereas IL-10 expression was lower (Fig.…”
Section: Papermentioning
confidence: 99%